correspondence to Philip a. Means the luis e. valcarcel (1932-1940) - Adanaqué Velásquez, Raul (2013)
This paper is a systematic study of the correspondence between two intellectuals very important to the history of Peru, Philip A. Means and Luis E. Valcarcel, U.S. and Peru, respectively. It took as its starting point the collection of information on the life and work of Means, this helped to complement the analysis of the letters sent by Means Valcarcel between the years of 1932-1940. The results of this research are reflected in the number of issues that were discussed by both intellectuals, all relevant to the history of Peru, but also revealed other information international. In sum, this study provides further insights on one of the little studied peruvianists from his correspondences with Peruvian intellectuals, in this case Luis E. Valcarcel.